The external appearance of the type Cercopis vulnerata (Rossi, 1807) (Homoptera: Cercopidae) in Iraq (Journal of the College of Basic Education, 2023)
The current study provides a description of the species 067418/14 ¡sau from the family of hoppy frogs.And with similar wings rank 11001001618 The study has shown a detailed descriptionand illustrative forms of the characteristics of the external appearance, especially the male and female sexes; It has also been recordedPlace and date of collection for this species. This species is a new record of the Iraqi insect group. PrepareThis species is a new record of the Iraqi insect group.Keywords: order Homoptera; Frogs, family, genus Ymba.IntroductionThe species of the genus (1807, c) m: f) are distinguished as:It contains the largest number of basic characteristics of the species of the family, which is the fact that it contains tentacles insideA cavity located on the side of the face and near the inner edge of the eye. It consists of four joints, namelyThe base has two short and wide pieces.The head is generally triangular in shape, the carapace is strong and striated, and the eyes are small and lateralThe two simple eyes are at the back of the head. The chest is broader than the headSmooth edges with an angular shape.belly short; The wing is circular, closed and particularly solitary with spots of various shapes, butred; The front legs are short and the hind legs are longer and have spinesOr more like claws, the number of which is 6, and the length is the result of the length of the leg 11518.